PERKEMBANGAN SYAIR JANTURAN JEJER PERTAMA PERKELIRAN WAYANG KULIT GAYA SURAKARTA - Subagya, Timbul (LP2M ISBI Bandung, 2018)
Wayang kulit, performance art in the culture of Javanese society, developed as a traditional art that navigates competition in the era of globalization. No wonder the Javanese people love it very much as a part of their lives. Although this art is a binding tradition, it appeared dynamic, evolved and changed over time. This article wrote about the phenomenon of change especially in the use ofjanturan literature. The dalang sang janturan as a narrative that told the situation in the wayang history. Every generation of dalang in Surakarta, used different versions ofpoetry.